PSYCHONEUROENDOCRINE ASPECTS OF POLYCYSTIC OVARY SYNDROME: FROM MECHANISMS TO CLINICAL CONSEQUENCES - A COMPREHENSIVE LITERATURE REVIEW - Ficek, Maciej; Gawęda, Wojciech; Łobodzińska, Wiktoria; Hamouta, Zuzanna; Adamczyk, Justyna (International Journal of Innovative Technologies in Social Science, 2026)
Purpose: Growing evidence conceptualizes Polycystic Ovary Syndrome (PCOS) as a complex psychoneuroendocrine condition whose consequences extend far beyond reproductive health. Research indicates that hyperandrogenism, insulin resistance, and chronic low-grade inflammation interact dynamically, affecting central nervous system functioning, stress responsiveness, and neurotransmitter regulation. These interrelated mechanisms contribute to a substantially increased vulnerability to depression, anxiety, disordered eating behaviors, and cognitive disturbances in women with PCOS. Dysregulation of both the hypothalamic-pituitary-ovarian (HPO) and hypothalamic-pituitary-adrenal (HPA) axes, together with adipokine imbalance and neuroinflammatory activity, provides a biologically coherent framework for understanding the heightened psychiatric burden associated with the syndrome. Importantly, psychological manifestations of PCOS are heterogeneous. Symptom severity and presentation are influenced by phenotype, metabolic status, body composition, age, and exposure to psychosocial and environmental stressors. Interventions targeting metabolic and inflammatory dysfunction, including insulin-sensitizing agents, anti-inflammatory strategies, lifestyle modification, and psychologically informed therapies have shown beneficial effects on mental health and quality of life, though responses vary considerably. These observations highlight the need for individualized, integrative treatment approaches and underscore the importance of longitudinal, mechanism-driven research to improve clinical outcomes. Methodology: A systematic review of the scientific literature was conducted, focusing on studies examining the psychoneuroendocrine mechanisms and mental health outcomes associated with Polycystic Ovary Syndrome (PCOS). The review primarily included clinical trials, observational studies, meta-analyses, and mechanistic research in human populations, with particular emphasis on endocrine, metabolic, neurobiological, and psychological outcomes. Findings: PCOS is consistently associated with a significantly increased burden of depression, anxiety, disordered eating, and cognitive complaints, mediated by interconnected psychoneuroendocrine mechanisms. The reviewed evidence indicates that hyperandrogenism, insulin resistance, and chronic low-grade inflammation disrupt neurotransmitter systems, stress-axis regulation, and brain connectivity, collectively contributing to mood dysregulation and reward-processing deficits. Interventions that improve metabolic function such as insulin sensitizers, anti-inflammatory strategies, and lifestyle modification, appear to alleviate psychological symptoms and improve quality of life, although effects vary by PCOS phenotype, metabolic status, age and treatment modality. Conclusions: Current evidence supports the role of Polycystic Ovary Syndrome as a condition with significant psychoneuroendocrine involvement, contributing to an increased risk of mood disorders, disordered eating, and cognitive dysfunction. However, further high-quality, longitudinal and mechanistically focused studies are required to elucidate the precise causal pathways linking endocrine and metabolic disturbances to brain function, and to determine optimal, personalized management strategies targeting both metabolic and mental health outcomes. These remain critical priorities for future research.